A 'Plug and Play' Platform for the Production of Diverse Monoterpene Hydrocarbon Scaffolds in Escherichia coli. Issue 9 (21st June 2016) - Leferink, Nicole G. H.; Jervis, Adrian J.; Zebec, Ziga; Toogood, Helen S.; Hay, Sam; Takano, Eriko; Scrutton, Nigel S.
Abstract: The terpenoids constitute one of the largest and most diverse classes of natural compounds with applications as pharmaceuticals, flavorings and fragrances, pesticides and biofuels. Synthetic biology is ideally placed to create new routes to this chemical diversity and facilitation of new compound discovery. The C10 monoterpenoids display a huge structural diversity produced from a single substrate, geranyl diphosphate, by a family of monoterpene cyclases and synthases (mTC/S). Here we employ a library of mTC/S in a single 'plug and play' platform system for the production of over 30 different monoterpenoids in Escherichia coli by fermentation on glucose. These products include several compounds never before produced in engineered microbes demonstrating the power of this approach to rapidly create routes to structural diversity . Abstract : A library of mTC/S is used in a single 'plug and play' platform for the production of over 30 different monoterpenoid scaffolds in Escherichia coli . These products include several compounds never before produced in engineered microbes demonstrating the power of this approach to rapidly create routes to structural diversity.